Student Digital Literacy in Singkawang School Through 5M Activities for Independent Learning - Andi Mursidi; Buyung Buyung; Eka Murdani (Universitas Negeri Makassar, 2022)
The Digital era is a period or Era where almost all fields in the order of life have been assisted by digital technology. In the context of education, digital competence can be interpreted as the use of technology in a convincing, appropriate, and safe way to achieve learning and educational goals. The research objective is to reveal the digital literacy skills of Singkawang City Junior High School students through 5M activities to support independent learning. The research method uses a quantitative approach. Researchers directly collect this study's source of data from the original subject, namely junior high school (SMP) students. This research was conducted in a junior high school in Singkawang City. The population of this study was as straight as junior high school students from grades VII-VIII from the age of 12 to 15 years, totaling 125. The sampling technique is probability sampling, namely area (cluster) sampling. The data collection technique used in this study was a test question. The instrument used to measure the variable of students' digital literacy ability was previously tested for validity and reliability. Data analysis technique to test research questions with ANOVA test with sig.0.05. The study results showed that the significant value data for each school was greater than 0.05, which means that the data is normally distributed. The five variants of the five schools that represent the population are the same (homogeneous). Digital literacy skills using 5M activities positively impact the learning process to support independent learning. There is a difference in the average digital literacy ability of junior high school students in Singkawang City after being given planting using 5M activities with a sig value of 0.00 < 0.05. But the results obtained by each school is different, but the results are still in the very good category